2020
DOI: 10.34172/aim.2020.55
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Umbilical Cord Serum Vitamin D Levels between Infants with Transient Tachypnea of the Newborn and those without Respiratory Distress

Abstract: Background: Transient tachypnea of the newborn (TTN) is one of the most frequent causes of respiratory distress in neonates. A relationship has been shown between vitamin D deficiency and respiratory disorders in neonates. This research was carried out to evaluate the serum level of vitamin D in TTN newborns and their mothers compared to the control group. Methods: This case-control research was conducted during 2016-2019 in a general hospital affiliated with Mashhad University of Medical Sciences, Iran. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The occurrence rates of RDS are presented by reference to the severity of vitamin D deficiency. Thus, we used the various levels in meta-analysis: a vitamin D level below 30 ng/ml in two studies [ 5 , 27 ], 20 ng/ml in six studies [ 11 , 15 , 25 , 27 , 29 , 30 ], 15 ng/ml in two studies [ 16 , 23 ], and 10 ng/ml in nine studies [ 11 , 17 , 22 , 24 , 25 , 28 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence rates of RDS are presented by reference to the severity of vitamin D deficiency. Thus, we used the various levels in meta-analysis: a vitamin D level below 30 ng/ml in two studies [ 5 , 27 ], 20 ng/ml in six studies [ 11 , 15 , 25 , 27 , 29 , 30 ], 15 ng/ml in two studies [ 16 , 23 ], and 10 ng/ml in nine studies [ 11 , 17 , 22 , 24 , 25 , 28 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of our study also show the effect of vitamin D in reducing lung damage and in ammatory processes. Numerous studies have suggested vitamin de ciency as a risk factor for respiratory problems in preterm infants, including RDSs and TTNs (4,12). Successful transition from fetal to neonatal life at delivery requires a series of extensive physiological changes in the cardiorespiratory system, leading to a change in the gas exchange pathway from the placenta to the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory distress syndrome (RDS) was defined as diffuse ground glass opacity in both lung fields on chest X-ray with respiratory difficulties, and transient tachypnea of newborn (TTN) was a sunburst appearance in both hilar areas on chest X-ray with tachypnea [ 21 ]. Because both respiratory disorders can be associated with vitamin D deficiency in neonates and the rates of very preterm infants as a potent risk factor of RDS were not significantly different between the two periods, we considered RDS and TTN as a respiratory illness in this study [ 11 , 12 , 13 , 14 ]. Hypocalcemia was defined as total serum calcium <7.5 mg/dL in the first week of life.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D plays a fundamental role in promoting various physiological functions, including the immune system, and prenatal and postnatal lung growth, as well as calcium and phosphorus homeostasis in neonates [ 7 , 8 ]. Vitamin D deficiency in neonates is related to diverse morbidities, such as late-onset hypocalcemia, sepsis, and respiratory illness, including respiratory distress syndrome (RDS) and transient tachypnea of newborn (TTN) in both preterm and term newborn infants [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%